STRESS DISTRIBUTION CAUSED BY TWO NEIGHBORING OUT-OF-PLANE LOCALLY COPHASALLY CURVED FIBERS IN A COMPOSITE MATERIAL - Cinar, N. T.; Kosker, R.; Akbarov, S. D.; Akat, E. (SPRINGER, 2010)
In the present paper, within the framework of a piecewise homogenous body model, with the use of the exact three-dimensional equations of elasticity theory, a method proposed earlier is developed for investigating the stress distribution caused by two neighboring out-of-plane locally cophasally curved fibers located along two parallel planes in an infinite elastic body. The body is loaded at infinity by uniformly distributed normal forces in the direction of fiber location. The self-equilibrated normal and shear stresses caused by the curved fibers are analyzed, and the influences of interaction between the fibers and of the geometric nonlinearity on the distribution of these stresses are studied. Numerical results for this interaction are obtained.
Keywords: composite; fibers; stress distribution; local curvature; INFINITE ELASTIC BODY; MECHANICS; Materials Science; Polymer Science